2020
DOI: 10.1038/s41598-019-57390-y
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of Anaplasma marginale acquisition and transmission by Dermacentor andersoni fed in vitro

Abstract: in this study, we describe a new in vitro tick feeding system that facilitates the study of ticks and tickborne pathogens. to optimize the system, we used Dermacentor andersoni and Anaplasma marginale as a tick-pathogen interaction model. Ticks were fed on bovine blood containing 10-fold dilutions of the pathogen to determine the effect of dose on tick infection rate. After feeding on infected blood, ticks were transferred to uninfected blood to stimulate bacterial replication within the tick vector. During st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…We demonstrated that artificial feeding is a suitable method for infecting ticks and could be utilized in various experimental studies that involve tick–pathogen interactions and pathogen transmissibility by ticks. Infection of hard ticks by artificial feeding was reported by other authors as well, emphasizing the efficiency of this method to successfully infect ticks with pathogens of viral, bacterial and parasitic origin [ 28 , 29 , 30 , 31 ]. This might also be a possible explanation for the different results between our study and that done by Lawrie et al (2004).…”
Section: Discussionmentioning
confidence: 90%
“…We demonstrated that artificial feeding is a suitable method for infecting ticks and could be utilized in various experimental studies that involve tick–pathogen interactions and pathogen transmissibility by ticks. Infection of hard ticks by artificial feeding was reported by other authors as well, emphasizing the efficiency of this method to successfully infect ticks with pathogens of viral, bacterial and parasitic origin [ 28 , 29 , 30 , 31 ]. This might also be a possible explanation for the different results between our study and that done by Lawrie et al (2004).…”
Section: Discussionmentioning
confidence: 90%
“…The observation of increased clock transcripts and reduced jak and pelle transcripts during transmission of A. phagocytophilum suggests responses from both vector and pathogen. The replication rate for A. marginale was noted to be significantly increased in ticks during this bacterial transmission from Dermacentor andersoni [ 59 ]. Therefore, it is reasonable to hypothesize that during transmission of A. phagocytophilum from I. scapularis to the murine host, ticks increase clock transcripts as a host response to activate jak and pelle expression, eventually to limit bacterial multiplication ( Figure 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…Fifty R. appendiculatus adults (25 males and 25 females) infected with T. parva were applied to the silicone membrane of the in vitro tick feeding system as described previously [ 23 ]. The ticks were allowed to feed initially on uninfected bovine blood at a packed cell volume of 10% containing 1× antibiotic/antimycotic solution (Sigma-Aldrich, St. Louis, MO, USA).…”
Section: Methodsmentioning
confidence: 99%